PENDAMPINGAN PENGEMBANGAN DIGITALISASI UMKM MASYARAKAT DESA WONOYOSO PEKALONGAN MENGHADAPI ERA NEW NORMAL - Arditya Prayogi; M.Ikhwanul Kirom (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The beginning of 2020 until the middle of the year is quite a tough year for all countries in all parts of the world. Since this pandemic, MSMEs have been one of the sectors that have been affected. In order for MSME actors to survive in the pandemic era, they must immediately adapt by digitizing MSMEs, because in this pandemic era, residents are starting to feel comfortable with transactions made digitally. The purpose of this MSME digitization activity is to help MSMEs to survive in the face of the pandemic era and be able to face the new normal era. This activity was carried out in 3 stages: first, the creation and distribution of MSME digitization guidebooks to MSME actors, secondly the development of MSME digitization, and a survey of the results of MSME digitization development. This activity was followed by MSME actors around the village of Wonoyoso. The method used in the implementation of the community service program regarding the digitization of MSMEs is in the form of socialization and assistance to MSMEs. Based on the survey results, it is known that MSME actors have started to use digital technology to develop their business.